Corruption as a Self-Fulfilling Prophecy: Evidence from a Survey Experiment in Costa Rica - Daniel W. Gingerich; Virgina Oliveros; Ana Corbacho; Mauricio Ruiz-Vega (Inter-American Development Bank (IDB), 2015)
An influential body of scholarship argues that corruption behaves as a selffulfilling prophecy. The idea of this work is that levels of corruption emerge endogenously as a result of a society-wide coordination game in which ther individual returns to corrupt behavior are a function of how disposed towards corruption the other members of society are perceived as being. An empirical implication of this logic is that if one were to exogenously perturb beliefs about societal levels of corruption upward, willingness to engage in corruption should increase as a consequence. The current paper evaluates this claim by utilizing an information experiment embedded in a large-scale household survey conducted in the Gran Área Metropolitana (GAM) of Costa Rica from October 2013 to April 2014 (n=4200). Changes in beliefs about corruption were induced via the random assignment of an informational display depicting the increasing percentage of Costa Ricans who have experienced or directly observed an act of corruption (from 2006 to 2011). The paper finds that, on average, assignment to this display (relative to the control condition) increased the probability that a respondent would be willing to pay a bribe to a police officer by approximately 0. 04 to 0. 08, thereby providing supporting evidence for the self-fulfilling prophecy hypothesis.
hdl:11319/6826
Keywords: D73; D84; C83; C90; 330; Corruption; Spillover effects; Survey experiments; Sensitive question techniques